1998
DOI: 10.1523/jneurosci.18-24-10481.1998
|View full text |Cite
|
Sign up to set email alerts
|

Expression Pattern and Neurotrophic Role of the c-fmsProto-Oncogene M-CSF Receptor in Rodent Purkinje Cells

Abstract: To investigate whether the c-fms proto-oncogene plays a role in the CNS, we examined its expression in mouse brain. We found that c-fms-positive Purkinje cells first appeared in caudal cerebellum at postnatal day 0 (P0) arranged in a parasagittal manner, and most Purkinje cells gradually became positive by P6. This differential expression was not seen from P7 to adulthood, and the parasagittal pattern until P5 was different from those of L7, zebrins, and the integrin beta1 subunit. No neuronal expression of c-… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
27
0

Year Published

1999
1999
2021
2021

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 29 publications
(29 citation statements)
references
References 50 publications
(53 reference statements)
2
27
0
Order By: Relevance
“…Other studies have shown that NMDA and GABA receptor subtypes are aberrantly expressed in sg/sg Purkinje cells (Luntz-Leybman et al, 1995;Nakagawa et al, 1996). The expression of calmodulin (Messer et al, 1990), the integrin ␤1 subunit (Murase and Hayashi, 1996), and c-fms (Murase and Hayashi, 1998) are developmentally arrested in staggerer. cfms expression may be particularly important for Purkinje cell survival, since it is the receptor for the proto-oncogene macrophage colony-stimulating factor, a putative trophic factor for Purkinje cells (Murase and Hayashi, 1998).…”
Section: Sg/sg Purkinje Cell Loss: An Indirect Results Of the Staggerementioning
confidence: 98%
See 1 more Smart Citation
“…Other studies have shown that NMDA and GABA receptor subtypes are aberrantly expressed in sg/sg Purkinje cells (Luntz-Leybman et al, 1995;Nakagawa et al, 1996). The expression of calmodulin (Messer et al, 1990), the integrin ␤1 subunit (Murase and Hayashi, 1996), and c-fms (Murase and Hayashi, 1998) are developmentally arrested in staggerer. cfms expression may be particularly important for Purkinje cell survival, since it is the receptor for the proto-oncogene macrophage colony-stimulating factor, a putative trophic factor for Purkinje cells (Murase and Hayashi, 1998).…”
Section: Sg/sg Purkinje Cell Loss: An Indirect Results Of the Staggerementioning
confidence: 98%
“…The expression of calmodulin (Messer et al, 1990), the integrin ␤1 subunit (Murase and Hayashi, 1996), and c-fms (Murase and Hayashi, 1998) are developmentally arrested in staggerer. cfms expression may be particularly important for Purkinje cell survival, since it is the receptor for the proto-oncogene macrophage colony-stimulating factor, a putative trophic factor for Purkinje cells (Murase and Hayashi, 1998). Only a relatively few sg/sg Purkinje cells in parasagittal bands in the vermis and lateral hemispheres express c-fms in staggerer at P6, whereas all Purkinje cells express c-fms by this age in controls.…”
Section: Sg/sg Purkinje Cell Loss: An Indirect Results Of the Staggerementioning
confidence: 99%
“…9 The CSF-1R is expressed on primitive multipotent hematopoietic cells, 10,11 mononuclear phagocyte progenitor cells, 12 monoblasts, promonocytes, monocytes, 5,6 tissue macrophages, 6,[13][14][15] osteoclasts, 16 B cells, 17,18 smooth muscle cells, 19 and neurons. 20,21 CSF-1R messenger RNA (mRNA) is expressed in Langerhans cells, 22 in the female reproductive tract, in oocytes and embryonic cells of the inner cell mass and trophectoderm, 23 in decidual cells, [24][25][26] and in cells of the trophoblast. 24,25 The expression of the CSF-1R on primitive hematopoietic cells that are unable to proliferate in vitro in response to CSF-1 alone 10,11 but are able to proliferate and differentiate if stimulated with combinations of CSF-1 and other hematopoietic growth factors 10,11,27 suggests that CSF-1R is involved in the regulation of more primitive hematopoietic cells than those that form macrophage colonies in vitro in response to CSF-1 alone.…”
Section: Introductionmentioning
confidence: 99%
“…This may result in neuronal self-protection through autocrine and paracrine M-CSF signaling. Some, but not all, studies have reported neuronal expression of the M-CSFR that varies depending on age and anatomic region (Murase and Hayashi, 1998;Raivich et al, 1998). Injury induces neuronal M-CSFR expression locally (Wang et al, 1999).…”
mentioning
confidence: 99%